Understanding private forest owners' conceptualisation of forest management: Evidence from a survey in seven European countries. (August 2017) - Feliciano, Diana; Bouriaud, Laura; Brahic, Elodie; Deuffic, Philippe; Dobsinska, Zuzana; Jarsky, Vilem; Lawrence, Anna; Nybakk, Erlend; Quiroga, Sonia; Suarez, Cristina; Ficko, Andrej
Abstract: Private forest owners' involvement in forest management has been frequently examined through the attitudes, values, beliefs, objectives and motivations associated with owning and managing forestland. Owners' views on forest management do not always align with those of policymakers who believe forest owners do not actively manage their forests. However, empirical studies on forest owners' conceptualisations of forest management are scarce. To determine how private forest owners in Europe conceptualise forest management, a survey (n = 1140) was undertaken in seven European countries (Portugal, France, the United Kingdom, the Czech Republic, Slovenia, Slovakia and Romania). The owners were asked to indicate their level of agreement with 19 pre-tested statements defining forest management on a five-point Likert scale. Classification and regression trees were used to explain the major factors that influenced owners' conceptualisations. Owners primarily conceptualised forest management as preserving forests for future generations and considered "a good business opportunity", "an opportunity to earn additional money" or a "source of subsidies" less important. Their understanding of forest management as a mixture of forest maintenance, ecosystem stewardship and economic activity does not match with alleged policy makers' views. Property size, age and Eastern/Western countries were the most relevant predictors of definitions of forest management. Small-scale forest owners from Western Europe considered ecosystem orientation more important, while owners from Eastern Europe considered economic aspects and forest maintenance more important. These differences might be associated with the socio-political system dynamics in Europe in the 20th century and changing values in post-modern society. Policymakers must be aware of the different forest management paradigms among forest owners in Eastern-Central and Western Europe when designing European forest policies. Highlights: Social representations theory challenges the definitions of passive and active forest owners. There is a contrast between policy makers' and forest owners' perception of forest management. Owners perceive maintenance of forests for future generations as active management. Western European owners have a more ecosystem-orientated view of forest management.